Variation in quality traits of newly developed Serbian wheat cultivars under different environmental conditions of Pannonian plain - Živančev, Dragan; Mirosavljević, Milan; Aćin, Vladimir; Momčilović, Vojislava; Mikić, Sanja; Torbica, Aleksandra; Jocković, Bojan (Italian Journal of Agronomy, 2021)
The introduction of new high-yielding wheat cultivars and the intensification of high year-to-year variability require an additional update of information about environmental effects on main wheat quality parameters lacking for newly released cultivars in Serbia. This study aimed to determine the effect of growing seasons on the technological properties of new Serbian wheat cultivars and examine the relationships among the quality traits in different growing seasons. The experiment was set up in three growing seasons (2016-17, 2017-18, and 2018-19). A total of 13 recently developed wheat cultivars in Serbia and the five most widespread local cultivars were evaluated to compare differences in end-use quality. Also, the influence of climatic conditions on technological quality was examined and relations among them. Modern Serbian cultivars have improved grain yield but lower technological quality than the widespread Serbian cultivars. Changes in farinograph resistance and degree of softening were related to the differences in growing seasons, cultivars, and their interaction, while growing seasons had the highest effect on bread volume and extensograph parameters energy and ratio resistance, and extensibility variation. Moreover, a strong positive correlation was found between protein content, sedimentation value, wet gluten content, water absorption with extensograph extensibility, and negative correlation with the second parameter of extensograph, resistance ratio, and extensibility. Highlights - The modern wheat cultivars showed improved grain yield but lower technological quality than widespread cultivars. - The growing seasons had the highest effect on bread volume and extensograph properties. - Grain yield was negatively related to protein content and bread volume.